2018
DOI: 10.1016/j.dib.2018.10.123
|View full text |Cite
|
Sign up to set email alerts
|

Data on SD-OCT image acquisition, ultrastructural features, and horizontal tissue shrinkage in the porcine retina

Abstract: The data presented in this article are related to the research paper entitled “Correlation of Spectral Domain Optical Coherence Tomography with Histology and Electron Microscopy in the Porcine Retina” (Xie et al., 2018) [2]. This research data highlights our technique for retinal fundus image acquisition during spectral domain optical coherence tomography (SD-OCT) in a large animal model. Low and high magnification electron micrographs are included to demonstrate the ultrastructural features of the porcine ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 2 publications
(2 reference statements)
1
31
0
Order By: Relevance
“…A subtle decrease in the grayscale reflectivity is apparent in Figure 1C corresponding to the same location. TEM revealed various cell types in the middle of the IPL, including endothelial cells (Xie et al, 2018 [Figure 2A]), fibrous astrocytes (Xie et al, 2018 [Figure 2B]), amacrine cells (Xie et al, 2018 [Figure 3A]), and Müller cells (Xie et al, 2018 [Figure 3B]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A subtle decrease in the grayscale reflectivity is apparent in Figure 1C corresponding to the same location. TEM revealed various cell types in the middle of the IPL, including endothelial cells (Xie et al, 2018 [Figure 2A]), fibrous astrocytes (Xie et al, 2018 [Figure 2B]), amacrine cells (Xie et al, 2018 [Figure 3A]), and Müller cells (Xie et al, 2018 [Figure 3B]).…”
Section: Resultsmentioning
confidence: 99%
“…Histologic analysis of the INL revealed a row of large cells with abundant cytoplasm in the middle to outer portion of the INL (Figure 2B, Xie et al, 2018 [Figure 4]). Immunofluorescence (Figure 3A) and immunohistochemical (Figure 3B) studies revealed that these large cells exhibited nuclear and cytoplasmic staining with anti-calbindin antibody (i.e., horizontal cells).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our understanding of factors directly affecting the vasomotor activity of retinal venules is seemingly limited to three studies in pigs, [19][20][21] which resemble human retinal morphology and structure. 22,23 Our previous study found that ET-1 causes marked constriction of porcine retinal venules through ET A receptors (ET A Rs) and extracellular Ca 2+ influx independent of L-type voltage-operated Ca 2+ channels. 20 We have also shown that hyperglycemia, a hallmark of diabetes, augments porcine venular constrictions to ET-1, U46619, and norepinephrine.…”
Section: Introductionmentioning
confidence: 99%